Analysis of Biomass Organic and Inorganic Carbon Stocks in Silokek Karst Geopark Area, Sijunjung Regency - Pertiwi, Vera; Chairul, Chairul; Syamsuardi, Syamsuardi (Universitas Islam Negeri Mataram, 2024)
Climate change caused by increasing greenhouse gas emissions, especially CO2, and deforestation, is an urgent global issue. The REDD+ program initiated by the UN aims to reduce carbon emissions and increase carbon storage in forests. This research aims to measure and analyze biomass and organic and inorganic carbon reserves in the Silokek Geopark area, Sijunjung Regency. The method used in this research is non-destructive sampling and using a destructive sampling method. Transects were carried out using the transect method using purposive sampling and were made in 10 plots 100 m long with square plots measuring 10x10 m for trees, 5x5 m for saplings, and 2x2 m for undergrowth. Next, the limestone samples used the chip sampling method and XRF analysis. The research results showed that the total organic biomass was 326,748 tons/ha, carbon reserves were 153,571 tons/ha, and carbon absorption was 563,607 tons/ha, which is categorized as high. The inorganic carbon content in the Silokek Geopark karst area is 4,908.07 tons/ha and inorganic carbon absorption is 18,012.60 tons/ha